2021
DOI: 10.1186/s40813-021-00197-z
|View full text |Cite
|
Sign up to set email alerts
|

Health monitoring of finishing pigs by secondary data use – a longitudinal analysis

Abstract: Background In Germany, animal welfare has become an increasingly important issue. Since 2006, German legislation demands self-monitoring of animal welfare by farmers, but there is a lack of prescribed indicators for governmental monitoring. Since recording of the health status through examinations on individual farms requires many resources, secondary data use is obvious. Therefore, this study deals with the overall evaluation and utilization of existing production data from the German pork pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
(6 reference statements)
0
11
0
1
Order By: Relevance
“…Since Grosse-Kleimann et al [2] found the initial body weight (IBW) on day one of the fattening period to be an important stratification criterion, only herds with IBW between 24 and 33.5 kg were chosen for further analyses. Additionally, data from pigs housed in pens with straw bedding or outdoor climate were excluded because the number of pens was too small to be representative (4 farms with exclusively straw bedding or outdoor climate).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since Grosse-Kleimann et al [2] found the initial body weight (IBW) on day one of the fattening period to be an important stratification criterion, only herds with IBW between 24 and 33.5 kg were chosen for further analyses. Additionally, data from pigs housed in pens with straw bedding or outdoor climate were excluded because the number of pens was too small to be representative (4 farms with exclusively straw bedding or outdoor climate).…”
Section: Methodsmentioning
confidence: 99%
“…Seven standardized health scores and one total score according to Grosse-Kleimann et al [2] were chosen as the target variables: mortality (MOR), average daily gain (ADG), feed conversion ratio (FCR), treatment frequency (TF) and meat inspection indicators associated with respiratory health (RESP), exterior injuries or alterations (EXT) and animal management (MANG). They are based on selected indicators from production data (Table 1) and were standardized on a zscale, with a mean of 0 and a standard deviation of 1.…”
Section: Health Scoresmentioning
confidence: 99%
See 3 more Smart Citations